Expression of Progenitor Cell Markers in the Glial-Like Cells of Epiretinal Membranes of Different Origins - Xiaohe Yan; Pål Andresen; Xhevat Lumi; Qingshan Chen; Goran Petrovski (Journal of Ophthalmology)
Purpose. To investigate the expression of progenitor cell markers (Sox2, Nestin, and Pax2) in idiopathic epiretinal membranes (iERMs) and nonidiopathic epiretinal membranes (niERMs) in relation to glial cell marker expression. Methods. ERMs were obtained from patients with iERMs and niERMs of different origins: proliferative diabetic retinopathy (PDR), proliferative vitreoretinopathy (PVR), and uveitis. The membranes were studied by flat-mount or sectional immunohistochemistry for expression of progenitor cell markers as well as glial (GFAP) and proliferation (Ki-67) markers. Results. Cells in the ERMs express strong GFAP, with strong Pax2 expression in the cell nuclei. Some of the GFAP-positive glial cells in all epiretinal membrane types colocalized with Sox2, Pax2, and Nestin. NiERMs are much more cellular than iERMs. Glial cells are more densely packed in all analyzed niERMs, whereas glial cells with long branches are found in the internal limiting membrane parts and the iERMs, which appear to form a local network by their processes. Conclusion. The GFAP-positive glial cells in ERMs are not pure glial cells, and some of them express progenitor cell markers, which indicate that these cells may have potential for self-renewal and differentiation into more glial or neuroglial type of cells.